Draft Annual Plan 1986-87 Vol-I Government of Tripura - Planning Commission (Planning Commission, 1986)
Even though a number of developmental schemes were taken up in different sectors, following the attainment of Statehood, Tripura remains at the end of the Sixth Five Year Plan very far behind the developed States of the country. The reasons are not far to seek. The State, with an area of 10,477 Sq. Kms. is among the smallest in the country. The population however is the second highest in the North Eastern Region, being next only to Assam. The resultant density of population coupled with an inadequate quantum of cultivable land has led to increasing pressure in the agricultural sector.
Government of Tripura
Government of Tripura